Water quality and aquaculture - Amoah, Philip; Drechsel, Pay (2023)
The quality of water used in aquaculture plays a dual role, it not only affects fish health and productivity but also influences environmental sustainability. This section presents practical insights and scientific benchmarks for managing aquaculture systems that use marginal or wastewater sources, particularly in developing countries. It explores common systems from Cambodia to Calcutta, where farmers use treated or untreated wastewater in fish and aquatic plant production. While some species like catfish and tilapia show resilience to low dissolved oxygen and nutrient-rich waters, optimal management is critical to balance nutrient inputs, prevent toxic buildup, and maintain fish growth and safety. The chapter outlines key risk mitigation strategies, such as species selection, mechanical aeration, depuration, and hygiene measures, to reduce human health risks from pathogens and bioaccumulated toxins. It also introduces a multi-barrier monitoring approach rooted in WHO’s sanitation safety planning. Environmental concerns from aquaculture particularly in dense systems like pangasius and shrimp farming in Vietnam are addressed through integrated farming models, sludge treatment, constructed wetlands, and market-driven incentives like certification schemes. By linking fish farming practices with water quality safeguards and policy incentives, the chapter offers a comprehensive guide to sustainable, low-risk aquaculture that supports both livelihoods and ecosystem protection.